Chromothripsis, DNA repair and checkpoints defects. (March 2022) - Simovic, Milena; Ernst, Aurélie
Abstract: Chromothripsis is a unique form of genome instability characterized by tens to hundreds of DNA double-strand breaks on one or very few chromosomes, followed by error-prone repair. The derivative chromosome(s) display massive rearrangements, which lead to the loss of tumor suppressor function and to the activation of oncogenes. Chromothripsis plays a major role in cancer as well as in other conditions, such as congenital diseases. In this review, we discuss the repair processes involved in the rejoining of the chromosome fragments, the role of DNA repair and checkpoint defects as a cause for chromothripsis as well as DNA repair defects resulting from chromothripsis. Finally, we consider clinical implications and potential therapeutic vulnerabilities that could be utilized to eliminate tumor cells with chromothripsis.